Palm tocotrienol-rich fraction supplementation suppressed stress-induced gastric oxidative stress in rats - Kamisah Y., Ibrahim A.A.I., Nafeeza M.I., Nur-Azlina M.F. (Journal of Applied Pharmaceutical Science)
Palm tocotrienol-rich fraction (TRF), an extract from palm oil containing both tocotrienol and tocopherol, is known for its antioxidant effect. The present study investigated the effect of palm TRF on the stomach using a water immersion restraint stress (WRS) model. Fortytwo male Sprague-Dawley rats were divided into three groups and were administered 60 mg/kg/d of palm TRF, α-tocopherol or vehicle only for 28 days. At the end of the treatment period, half of the rats from each group were subjected to WRS for 3.5 hours, after which the rats were sacrificed. The stomachs were then examined for lesions and measured for thiobarbituric acidreactive substance content and xanthine oxidase activity. Rats exposed to WRS showed gastric mucosal lesions. Pretreatments of the palm TRF and α-tocopherol reduced the occurrence of the lesions. WRS also increased gastric malondialdehyde content and xanthine oxidase activity significantly, but the increase in the oxidative stress parameters were significantly suppressed by both vitamin E pretreatments. However, the effects of palm TRF and α-tocopherol on the parameters measured were not different. In conclusion, palm TRF has the ability to protect against gastric mucosal injury, likely via its ability to inhibit oxidative stress.
Keywords: Tocotrienol, water immersion restraint stress, lipid peroxidation, gastric lesion, xanthine oxidase